AI Personalization, Brand Experience, and Religiosity in Indonesian Muslim E-Commerce - Eka Kadharpa Utama Dewayani; Dustin Tarinque Loreño (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study explores how AI-enabled features, interaction, information, accessibility, and customization influence brand experience, brand preference, and repurchase intention in Indonesia’s Muslim fashion e-commerce. Guided by the Stimulus-Organism-Response (S-O-R) framework, AI functionalities are conceptualized as stimuli, brand experience as the internal state, and preference and repurchase as behavioral responses. Religiosity is introduced as a moderator, assessing how religious commitment strengthens the link between brand preference and repurchase behavior. Data from 384 Muslim consumers reveal that all four AI features significantly enhance brand experience, which in turn drives preference and repurchase intention. Religiosity positively moderates the preference-repurchase link, underscoring the importance of value alignment in Islamic markets. These findings contribute to digital marketing and Islamic consumer behavior literature by highlighting how AI-driven personalization must be culturally attuned. For practitioners, the study offers insights into designing faith-sensitive AI features that build trust, engagement, and loyalty among Muslim consumers in rapidly growing online markets.